A new species of Laccobius Erichson and additional faunistic records of the genus from China, with a key to subgenus Glyptolaccobius Gentili (Coleoptera: Hydrophilidae) - Zhang, Ruijuan; Jia, Fenglong (Zootaxa, 2017)
A new species of water scavenger beetle, Laccobius (Glyptolaccobius) yinziweii sp. nov. is described from Yunnan, China. Diagnostic characters are illustrated. Laccobius (Cyclolaccobius) nitidus Gentili, 1984 is reported from Guizhou, Laccobius (Microlaccobius) hammondi Gentili, 1984 from Hubei, and Laccobius (s. str.) inopinus Gentili, 1980 from Guizhou for the first time. Additionally, an identification key to Laccobius (Glyptolaccobius) of the world is updated.